Knowledge spillover effects in German knowledge-intensive industries - Hájek, Petr; Stejskal, Jan (2016)
It is widely assumed that firms collaborating in Research and Development (R&D) activities benefit from knowledge spillovers. However, there has been little discussion about the synergistic effects of knowledge spillovers and R&D collaboration.This paper examines the role of three types of knowledge spillovers, namely internal, market and institutional.R&D collaboration mediates the knowledge spillovers effects in the proposed structural equation models.This study demonstrates that German knowledge-intensive firms prefer internal knowledge transfer and market R&D collaboration, respectively.The empirical evidence shows that these tools promote innovation performance. The highest effects are obtained for the combination of market knowledge spillovers (.043***) and market R&D collaboration (.066***). This research thus provides justification for this strategy.It also shows that public financial support represents an effective measure for establishing R&D collaboration based on knowledge spillovers generated in the communication within the firm, in the market and with public institutions.The support of market and institutional R&D collaboration seems to be particularly important.